2020
DOI: 10.1097/md.0000000000021152
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein testing to guide antibiotic prescribing for COPD exacerbations

Abstract: Background: The use of antibiotics in the acute exacerbations of chronic obstructive pulmonary disease (COPD) remains controversial. Serum C-reactive protein (CRP), a sensitive biomarker for systemic inflammation and tissue damage, is a good indicator of lower respiratory tract bacterial infection. However, due to the small sample size of the existing studies, the clinical value of CRP in guiding the use of acute exacerbation of chronic obstructive pulmonary disease (AECOPD) antibiotics is insuffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In this study, it was also found that the proportion of patients who used antibiotics ≥ 14 d in infection group was significantly higher than that in non-infection group, and use time of antibiotics ≥ 14 d was an independent influencing factor for lower respiratory tract fungal infection in AECOPD patients. Urinary catheterization and tracheal intubation are common invasive operations that can damage the urinary tract mucosa and respiratory mucosa to a certain extent, and raise the risk of infection by pathogenic microorganism such as fungi [16]. It has been reported that blood glucose elevation is an independent influencing factor for the death of inpatients with COPD, and this was once again confirmed in this study [17].…”
Section: Discussionsupporting
confidence: 81%
“…In this study, it was also found that the proportion of patients who used antibiotics ≥ 14 d in infection group was significantly higher than that in non-infection group, and use time of antibiotics ≥ 14 d was an independent influencing factor for lower respiratory tract fungal infection in AECOPD patients. Urinary catheterization and tracheal intubation are common invasive operations that can damage the urinary tract mucosa and respiratory mucosa to a certain extent, and raise the risk of infection by pathogenic microorganism such as fungi [16]. It has been reported that blood glucose elevation is an independent influencing factor for the death of inpatients with COPD, and this was once again confirmed in this study [17].…”
Section: Discussionsupporting
confidence: 81%
“…Studies have shown that a high CRP level at discharge is an independent predictor of further exacerbation requiring hospital admission for AECOPD, and CRP can serve as an indicator for evaluating the prognosis of AECOPD patients (Chang et al, 2014). Meanwhile, CRP is also considered an effective biological indicator for guiding antibiotic treatment in AECOPD patients, and many studies have advocated for the use of antibiotic treatment for patients with higher levels of CRP (Butler et al, 2019;An et al, 2020). Consistent with this, the subgroup analysis results of this study also showed that for AECOPD patients with high CRP levels, antibiotic treatment can reduce the acute exacerbation rate 30 days after discharge, even if the patient does not have any obvious signs of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with acute exacerbations, CRP levels tend to increase, a conclusion reached after testing about 36 biomarkers, with good diagnostic accuracy, increased levels correlating with raised white blood cell count, and a purulent expectorate because of bacterial infection [ 6 ]. Studies have proposed that serial measurements of plasma CRP can lead to favorable outcomes of COPD when treated with inhaled corticosteroids and antibiotics [ 7 , 8 ]. Furthermore, CRP is also thought to be a contributing factor in determining the prognosis of COPD, as such increased levels are not only seen in acute exacerbations but also chronic, stable disease, indicating an ongoing low-level, underlying inflammatory activity, even when compared to smokers without the disease [ 9 ].…”
Section: Introductionmentioning
confidence: 99%